Understanding the cross-country effects of US technology shocks - Wataru Miyamoto; Thuy Lan Nguyen (Bank of Canada, 2017)
Business cycles are substantially correlated across countries. Yet most existing models are not able to generate substantial transmission through international trade. We show that the nature of such transmission depends fundamentally on the features determining the responsiveness of labor supply and labor demand to international relative prices. We augment a standard international macroeconomic model to incorporate three key features: a weak short-run wealth effect on labor supply, variable capital utilization, and imported intermediate inputs for production. This model can generate large and significant endogenous transmission of technology shocks through international trade. We demonstrate this by estimating the model using data for Canada and the United States with limited-information Bayesian methods. We find that this model can account for the substantial transmission of permanent US technology shocks to Canadian aggregate variables such as output and hours, documented in a structural vector autoregression. Transmission through international trade is found to explain the majority of the business cycle co-movement between the United States and Canada.
Keywords: F41; F44; F62; E30; 330; Business fluctuations and cycles; Economic models; International topics